2011
DOI: 10.4194/1303-2712-v11_3_22
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, effects of early weaning of sea bass (D. labrax) by microparticulate food on larval development and digestive enzyme activities, acid protease and alkaline protease were investigated until day 40. Larval rearing was conducted in closed sea water systems. Experiments were triplicated on 3 different weaning protocol that introduced on day 15 (MD15), day 20 (MD20) and day 25 (MD25) and also no microparticulate diet (MD) distributed in the control group. At the end of the experiment at 40-day, larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…These results are consistent with previous studies on freshwater species such as Nile tilapia [53], grass carp, and African catfish [54], B. subtilis possesses the capacity to improve the breakdown of nutrients in the gut, resulting in increased energy availability for fish growth. Previous studies have demonstrated that probiotics can generate a diverse array of exo-enzymes and enhance the functioning of the digestive enzymes within the gut [55]. Furthermore, the inclusion of dietary probiotics can have an impact on the composition of the intestinal microbiota in fish.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies on freshwater species such as Nile tilapia [53], grass carp, and African catfish [54], B. subtilis possesses the capacity to improve the breakdown of nutrients in the gut, resulting in increased energy availability for fish growth. Previous studies have demonstrated that probiotics can generate a diverse array of exo-enzymes and enhance the functioning of the digestive enzymes within the gut [55]. Furthermore, the inclusion of dietary probiotics can have an impact on the composition of the intestinal microbiota in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Ketika larva beralih dari mengonsumsi makanan alami ke pakan buatan, larva harus terlebih dahulu menyesuaikan (menyapih) untuk membiasakan makan makanan buatan dan mencernanya dengan baik. Larva ikan kakap (Dicentrarchus labrax) yang terlalu dini diberi pakan buatan mikropartikulat yaitu pada hari ke-15 memiliki pertumbuhan dan sintasan yang rendah (Suzer et al, 2011). Menurut (Amornsakun et al, 2005), larva ikan betok mulai mengkonsumsi pakan buatan pada umur 16 hari, dan (Yulintine et al, 2012) menyarankan untuk memulai pemberian pakan buatan pada hari ke 25 setelah menetas berdasarkan perkembangan sistem pencernaan.…”
Section: Pendahuluanunclassified
“…This disparity arises from different methodologies used in analyzing data, particularly in the collection of digestive tract secretions from other vertebrates (Assan et al, 2022). Examining the presence and activity levels of digestive enzymes provides valuable insights into food acceptance, the rate of fish larvae development, digestive efficiency, and ultimately, survival rates (Suzer et al, 2008). Research, such as that undertaken by Solovyev et al (2014), demonstrates that analyzing the activity of et al, 2015) digestive enzymes in fish offers valuable understanding of their role in ecosystems and feeding habits under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes are released into the intestinal tract, increasing the overall pool of enzymes. As a result, they break down food nutrients, making them more accessible to the host fish through the resulting metabolites they secrete (Wang, 2007;Suzer et al, 2008;Zhou et al, 2009). Research on fish digestive health has substantially contributed to understanding nutrient digestion, absorption, and utilization (Table 1) (Burns et al, 2016;Yan et al, 2016;Nie et al, 2017;Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation